2013
DOI: 10.1080/14623943.2012.732935
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice in initial teacher training: critiques and perspectives

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
44

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 21 publications
1
49
0
44
Order By: Relevance
“…Likewise, Rodgers (2002) raised four key issues that arise from the loss of clear definition of reflection: 1) difficulty in differentiating reflection from other forms of thought processes, 2) issues with the assessment of reflective skills, 3) absence of common understanding and language that would facilitate conversation about reflection and its practice, and 4) challenge of studying the impact of reflective practice on teacher education and professional development. Collin, Karsenti, and Komis (2013) corroborated these assertions in their article. They concluded that the lack of consensus on the concept and terminology for reflective practice results to the difficulty in operationalizing its methodology and, consequently, its evaluation, which subsequently, obstructs empirical research.…”
Section: Concerns and Issues With Reflection And Reflective Writingsupporting
confidence: 78%
“…Likewise, Rodgers (2002) raised four key issues that arise from the loss of clear definition of reflection: 1) difficulty in differentiating reflection from other forms of thought processes, 2) issues with the assessment of reflective skills, 3) absence of common understanding and language that would facilitate conversation about reflection and its practice, and 4) challenge of studying the impact of reflective practice on teacher education and professional development. Collin, Karsenti, and Komis (2013) corroborated these assertions in their article. They concluded that the lack of consensus on the concept and terminology for reflective practice results to the difficulty in operationalizing its methodology and, consequently, its evaluation, which subsequently, obstructs empirical research.…”
Section: Concerns and Issues With Reflection And Reflective Writingsupporting
confidence: 78%
“…Prueba de ello es la inclusión de la capacidad de reflexión y de análisis crítico como una competencia clave en un cada vez mayor número de programas académicos de formación del profesorado (Collin, Karsenti y Komis, 2013). …”
Section: Hacia Un Practicum Reflexivounclassified
“…En su tesis doctoral Weber (2013) asevera que no existe una definición precisa de reflexión, estando por lo tanto de acuerdo con un gran número de autores (Collin, et al, 2013;Hickson, 2011;Larrivee, 2008;Lee, 2008;Marcos, Sanchez, y Tillema, 2011;Thorpe, 2004 e. Requiere intencionalidad (Hatton y Smith, 1995;Zeichner y Liston, 1996;Sanjurjo, 2002;Ng, Lan, y Thye, 2004).…”
Section: Mason Y Klein (2013)unclassified
See 2 more Smart Citations